Development of novel kinetic model based on microbiome and biochar for in-situ remediation of total petroleum hydrocarbons (TPHs) contaminated soil. (May 2023) - Saeed, Maimona; Ilyas, Noshin; Bibi, Fatima; Shabir, Sumera; Jayachandran, Krish; Sayyed, R.Z.; Shati, Ali A.; Alfaifi, Mohammad Y.; Show, Pau Loke; Rizvi, Zarrin Fatima
Abstract: A novel kinetic model has been developed to explain the degradation of total petroleum hydrocarbons. Microbiome engineered biochar amendment may result in a synergistic impact on degradation of total petroleum hydrocarbons (TPHs). Therefore, the present study analyzed the potential of hydrocarbon-degrading bacteria A designated as Aeromonas hydrophila YL17 and B as Shewanella putrefaciens Pdp11 morphological characterized as rod shaped, anaerobic and gram-negative immobilized on biochar, and the degradation efficiency was measured by gravimetric analysis and gas chromatography-mass spectrometry (GC-MS). Whole genome sequencing of both strains revealed the existence of genes responsible for hydrocarbon degradation. In 60 days remediation setup, the treatment consisting of immobilization of both strains on biochar proved more efficient with less half-life and better biodegradation potentials compared to biochar without strains for decreasing the content of TPHs and n-alkanes (C12 –C18 ). Enzymatic content and microbiological respiration showed that biochar acted as a soil fertilizer and carbon reservoir and enhanced microbial activities. The removal efficiency of hydrocarbons was found to be a maximum of 67% in soil samples treated with biochar immobilized with both strains (A + B), followed by biochar immobilized with strain B 34%, biochar immobilized with strain A 29% and with biochar 24%, respectively. A 39%, 36%, and 41% increase was observed in fluorescein diacetate (FDA) hydrolysis, polyphenol oxidase and dehydrogenase activities in immobilized biochar with both strains as compared to control and individual treatment of biochar and strains. An increase of 35% was observed in the respiration rate with the immobilization of both strains on biochar. While a maximum colony forming unit (CFU/g) was found 9.25 with immobilization of both strains on biochar at 40 days of remediation. The degradation efficiency was due to synergistic effect of both biochar and bacteria based amendment on the soil enzymatic activity and microbial respiration. Graphical abstract: Image 1 Highlights: Effects of biochar and oil degrading bacteria studied on biodegradation of TPHs. Novel kinetic model developed based on microbiome and biochar. Biodegradation of total petroleum hydrocarbons affected by both combination of biochar and bacteria. Soil microbial activity, respiration rate and enzymes play a key role in TPHs removal mechanism.